Chlamydomonas Flavodiiron Proteins Facilitate Acclimation to Anoxia During Sulfur Deprivation - Jokel, Martina (Plant Cell Physiol, 2015)
The flavodiiron proteins (FDPs) are involved in the detoxification of oxidative compounds, such as nitric oxide (NO) or O(2) in Archaea and Bacteria. In cyanobacteria, the FDPs Flv1 and Flv3 are essential in the light-dependent reduction of O(2) downstream of PSI. Phylogenetic analysis revealed that two genes (flvA and flvB) in the genome of Chlamydomonas reinhardtii show high homology to flv1 and flv3 genes of the cyanobacterium Synechocystis sp. PCC 6803. The physiological role of these FDPs in eukaryotic green algae is not known, but it is of a special interest since these phototrophic organisms perform oxygenic photosynthesis similar to higher plants, which do not possess FDP homologs. We have analyzed the levels of flvA and flvB transcripts in C. reinhardtii cells under various environmental conditions and showed that these genes are highly expressed under ambient CO(2) levels and during the early phase of acclimation to sulfur deprivation, just before the onset of anaerobiosis and the induction of efficient H(2) photoproduction. Importantly, the increase in transcript levels of the flvA and flvB genes was also corroborated by protein levels. These results strongly suggest the involvement of FLVA and FLVB proteins in alternative electron transport.